Tragedy of too many - Ogale, S.L. (Bombay, 1969)
Like an individual, every generation has its own destiny; problems posed vary from generation to generation. Overriding effects of such problems have, sometimes, a lingering spell and thus baffle more than one generation; some problems, however, have such a far-reaching and frightening effect, that they put a particular generation almost out of its wits; they demand all energies and test the forbearance of its people; their implications are, indeed, very deep and they do have a persistence over time. Over-population is one such problem of our time.
Keywords: Populations